Importancia de una planeación tributaria en empresas del sector minero en Boyacá. (2022)
This article discusses the importance and strategies of reducing taxes for microenterprises in the mining sector in Boyacá, which seek to reduce the tax impact and improve their activity. The methodology is documentary, mixed approach, and descriptive. Defining the main fiscal, social, and environmental responsibilities and the tax benefits that this sector can apply. Taking into account that the collection of taxes is important in the economy of a country, it is sought that companies can optimize their tax burdens in accordance with the provisions of current regulations. Concluding with a tax projection that allows considering the tax burden and the affectation of payments according to a business tax structure and the supporting documentation fiscally required, in order to avoid generating rejection of the costs and deductions that can be presented in the operation of the company, generating a decrease in the tax burden and promoting the formality of this sector.